Nano Ag and nano CuI co-loaded WO3-x material, preparation method and application

The nano-Ag and nano-CuI co-loaded WO3-x material addresses the challenges of high-temperature requirements and catalyst recyclability in carboxylation reactions by enabling efficient CO2 activation and reaction at medium temperatures, achieving high yields and recyclability.

CN119114114APending Publication Date: 2024-12-13JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311635668.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-01
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing catalytic systems for the carboxylation of alkynes with CO2 require harsh conditions and are difficult to recycle, as they need high temperatures and complex catalysts with auxiliary agents, and CO2's stable chemical properties make it challenging to activate.

Method used

A nano-Ag and nano-CuI co-loaded WO3-x material is developed, where WO3-x nanosheets are loaded with Ag and CuI, allowing for the carboxylation of alkynes with CO2 under normal pressure and medium temperature conditions, utilizing the synergistic effects of Ag and CuI to activate the C(sp)-H bond and enhance catalyst recyclability.

Benefits of technology

The composite material achieves a good yield in the carboxylation reaction of alkynes with CO2, maintaining a medium yield after 5 cycles and demonstrating good recyclability, with Ag and CuI providing active sites and enhancing the catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114114A_ABST
    Figure CN119114114A_ABST
Patent Text Reader

Abstract

The invention discloses a nano Ag and nano CuI co-loaded WO3-x material as well as a preparation method and application thereof. The material comprises a WO3-x nanosheet, and Ag and CuI are loaded on the WO3-x nanosheet; in the material, the content of Ag is 0.01%-10%, the content of CuI is 0.05%-10%, and the content of WO3-x is 80%-99.4%. The Ag / CuI / WO3-x material has rich oxygen vacancies and can increase adsorption to gas and organic substrate molecules, the silver element exists in the form of Ag (0 valence), the copper element in CuI exists in the form of Cu (I valence) and is an active site for activating a reactant alkyne C (sp)-H bond, so that the C-H bond is easy to break, proceeding of carboxylation esterification reaction of alkyne and CO2 under synergistic catalysis of WO3-x is promoted, and the reaction efficiency is improved. The carboxylation reaction of end alkyne and CO2 under the conditions of normal pressure and medium temperature is realized, and a better yield is obtained; when the catalyst is applied to catalysis of carboxylation reaction of alkyne and CO2, high product yield is obtained, and the catalyst has potential application and popularization values and has an important promotion effect on development of a CO2 resource reutilization technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nano-Ag and nano-CuI co-loaded WO 3-x The invention relates to materials, preparation methods and applications, belonging to the technical field of micro-nano materials. Background Art

[0002] The development of CO2 emission reduction technology, capture and storage technology, and resource recycling technology plays an important role in promoting the development of CO2. Among them, using CO2 as a carbon resource and synthesizing high-value-added chemicals through chemical conversion is one of the most competitive technical routes to achieve green carbon cycle.

[0003] At present, the chemical transformation and resource utilization of CO2 using various chemical reactions have been widely and deeply studied. For example, CO2 can be converted into various valuable chemicals by hydrogenation reaction. Under controlled conditions, formic acid and its formic acid derivatives, formaldehyde, methanol, etc. can be obtained; CO2 can react with olefins to prepare unsaturated fatty acids and their derivatives; react with alkynes to prepare acetylenic acid and its derivatives; react with phenol to prepare salicylic acid; react with alcohols or epoxy compounds to prepare linear or cyclic carbonate compounds and their polymers; and use reductive acylation reactions to prepare various aldehyde compounds. Alkynoic acid and acetylenic acid ester derivatives can be used as important raw materials or intermediates for organic synthesis to prepare functionally rich and structurally diverse hybrid compounds such as furan, pyrazole, pyrrole, indole, benzopyridine, etc.

[0004] Alkynoic acid can be prepared by carboxylation of alkynes containing terminal acetylenic hydrogen and CO2. If there is a halogenated hydrocarbon in the reaction system, the corresponding acetylenic acid derivative can be obtained. In the presence of a silver or copper catalyst, the addition of an excess of base with an auxiliary effect can achieve the reaction of CO2 and alkyne, and the addition of a halogenated hydrocarbon such as iodinated n-butane can obtain the corresponding acetylated ester derivative. However, in addition to the addition of a catalyst, the realization of this type of reaction usually requires the addition of auxiliary agents such as ligands. The catalytic conditions are harsh and complex, and it is difficult to achieve the recycling of the catalyst. CO2 is a molecule with extremely stable chemical properties, with very low molecular energy (ΔH0 ~ -400KJ / mol) and a very stable structure. It needs to absorb a lot of energy to participate in chemical synthesis as a raw material. Therefore, the alkyne carboxylation reactions reported so far all need to be heated to a relatively high temperature.

[0005] In order to realize the carboxylation reaction of alkynes with CO2, it is necessary to develop a catalytic system that can activate both the C(SP)-H bond and the CO2 carbon molecule. Tungsten oxide has a large number of variable valence states, and its microscopic morphology and electronic structure have good designability. WO with rich oxygen defects can be prepared by chemical means. 3-xIt not only exhibits good electrochemical and photocatalytic properties by regulating the valence band electronic structure, but also can utilize abundant oxygen defect sites to increase the adsorption of gas and organic substrate molecules, making it a good catalyst carrier. Summary of the invention

[0006] The purpose of the present invention is to provide a nano-Ag and nano-CuI co-loaded WO 3-x Materials, preparation methods and applications, by using WO 3-x As the carrier, Ag / CuI / WO was designed and prepared. 3-x The catalyst was applied to catalyze the carboxylation reaction of alkynes with CO2, and good results were achieved.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A nano-Ag and nano-CuI co-loaded WO 3-x Material, the material comprising WO 3-x Nanosheets, the WO 3-x The nanosheets are loaded with Ag and CuI; in the material, the content of Ag is 0.01-10%, the content of CuI is 0.05-10%, and the content of WO is 3-x The content is 80-99.4%.

[0009] The above nano-Ag and nano-CuI are co-loaded with WO 3-x The method for preparing the material comprises the following steps:

[0010] S1. Preparation of WO 3-x Nanosheets;

[0011] S2. WO 3-x The nanosheets, AgNO3, KI and CuSO4 were dispersed in a solvent, and then ethanol and dimethylformamide solution were added dropwise. After stirring, the product was centrifuged and dried and calcined to obtain Ag / CuI / WO. 3-x Nanomaterials.

[0012] Preferably, in step S1, WO 3-x The preparation method of the nanosheet is as follows: dissolving sodium tungstate dihydrate, adding acid solution and heating, and then washing and drying the product.

[0013] Preferably, the acid solution is any one of concentrated hydrochloric acid, concentrated nitric acid and concentrated sulfuric acid.

[0014] Preferably, WO 3-x During the preparation of the nanosheets, the acid solution is added and heated to 150-220°C and kept warm for 4-7 hours.

[0015] Preferably, the ratio of sodium tungstate dihydrate to acid solution is: (1-5) mmol: (15-30) mL.

[0016] Preferably, in step S2, WO 3-x The mass ratio of nanosheets, AgNO3, KI, and CuSO4 is:

[0017] (50-150):(0.6-4):(6-12):(3-10).

[0018] Preferably, in step S2, calcination is performed under an atmosphere of 1-10% hydrogen and 90-99% argon or nitrogen.

[0019] Preferably, in step S2, the calcination temperature is 150-300°C.

[0020] The above nano-Ag and nano-CuI are co-loaded with WO 3-x Nano-Ag and nano-CuI prepared by any of the above-mentioned preparation methods are co-loaded with WO 3-x Application of materials in catalyzing the acidification reaction of alkynes with CO2.

[0021] The beneficial effects of the present invention are:

[0022] The Ag / CuI / WO 3-x The composite material has abundant oxygen defects, which can increase the adsorption of gas and organic substrate molecules, and is a good catalyst. Among them, the silver element exists in the form of Ag (0 valence), and the copper element in CuI exists in the form of Cu (I valence), which is the active site for activating the C (sp)-H bond of the reactant alkyne, making the CH bond easy to break, promoting the reaction of WO 3-x The synergistic catalytic carboxylation and esterification reaction of alkynes and CO2 was carried out, realizing the carboxylation reaction of terminal alkynes and CO2 under normal pressure and medium temperature conditions, and a good yield was obtained; and the catalyst has good recyclability and still maintains a medium yield after 5 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Ag / CuI / WO obtained in Example 1 3-x XRD patterns corresponding to nanomaterials;

[0024] Figure 2 Ag / CuI / WO obtained in Example 1 3-x The corresponding SEM images of nanomaterials;

[0025] Figure 3 for Ag / CuI / WO 3-x (Ag 0.5%CuI 7.1%) recycling effect diagram. DETAILED DESCRIPTION

[0026] The present invention will be specifically described below in conjunction with the accompanying drawings and embodiments.

[0027] Example 1

[0028] (1)WO 3-x Preparation of nanosheets

[0029] 1.32g (4mmol) sodium tungstate dihydrate was dissolved in 25mL deionized water, and then 20mL concentrated sulfuric acid (commercially available, mass fraction 98%) was added under strong stirring. The solution was added to a polytetrafluoroethylene reactor, heated to 200℃, and kept warm for 4h. After the reaction was completed, it was washed and dried to obtain a sample, namely WO 3-x Nanosheets.

[0030] (2) Nano-Ag and Nano-CuI Co-loaded WO 3-x Preparation of composite nanomaterials

[0031] 100g WO 3-x The nanomaterials and 0.85 g (5 mmol) of AgNO3, 8.3 g (50 mmol) of KI, and 6.4 g (40 mmol) of CuSO4 were dispersed in 40 mL of deionized water, and 15 mL of ethanol and 10 mL of dimethylformamide were slowly added under magnetic stirring. The magnetic stirring was continued for 5 h, and then the sample was dried by centrifugation in a vacuum. The sample was calcined at 170 ° C in a 5% hydrogen + 95% argon or nitrogen atmosphere to obtain Ag / CuI / WO 3-x Nanomaterials, and WO 3-x The content is 92.4%, the Ag content is 0.5%, and the CuI content is 7.1%.

[0032] The Ag / CuI / WO 3-x The XRD spectrum of nanomaterials is as follows Figure 1 As shown, WO 3-x The XRD pattern of WO corresponds to PDF#53-0343, which can be indexed as tetragonal tungsten oxide. 3-x with Ag / CuI / WO 3-x By comparison, it was found that the XRD spectrum of Ag / CuI / WO3-x catalyst showed strong CuI diffraction peak signals, and its diffraction peaks appeared at 25.268°, 29.258°, 41.853°, and 51.881°, corresponding to the cubic system of CuI. The XRD spectrum of the sample did not find the diffraction peak of Ag. The reason is that the Ag content is low, so there is no Ag diffraction peak in the XRD spectrum. In order to further study the Ag / CuI / WO 3-x The morphology of the samples and the SEM images of the samples were tested, such as Figure 2As shown in the figure, the prepared sample basically maintains the nanosheet morphology, and the surface of the nanosheet is rough and uneven due to the attachment of CuI and Ag. The thickness of the nanosheet also increases from about 5nm to about 10nm, and the nanosheet maintains a relatively regular square shape with a size of about 100nm.

[0033] Example 2

[0034] (1)WO 3-x Preparation of nanosheets

[0035] 1.32g (4mmol) sodium tungstate dihydrate was dissolved in 25mL deionized water, and then 22mL concentrated sulfuric acid (commercially available, mass fraction 98%) was added under strong stirring. The solution was added to a polytetrafluoroethylene reactor, and the temperature was raised to 175℃ and kept for 5h. After the reaction was completed, the sample was washed and dried to obtain WO 3-x Nanosheets.

[0036] (2) Nano-Ag and Nano-CuI Co-loaded WO 3-x Preparation of composite nanomaterials

[0037] 100g WO 3-x Nanomaterials and 1.7g (10mmol) AgNO3, 11.2g (70mmol) KI, 8g (50mmol) CuSO4 were dispersed in 60mL deionized water, and 20mL ethanol and 15mL dimethylformamide were slowly added under magnetic stirring, and magnetic stirring was continued for 5h, and then the sample was dried by centrifugation and vacuum drying. The sample was calcined at 180℃, 5% hydrogen + 95% argon or nitrogen atmosphere to obtain Ag / CuI / WO 3-x Nanomaterials, and WO 3-x The content is 90.3%, the Ag content is 1%, and the CuI content is 8.7%.

[0038] Example 3

[0039] (1)WO 3-x Preparation of nanosheets

[0040] 1.32g (4mmol) sodium tungstate dihydrate was dissolved in 28mL deionized water, and then 20mL dilute nitric acid (commercially available, mass fraction 98%) was added under strong stirring. The solution was added to a polytetrafluoroethylene reactor, and the temperature was raised to 195℃ and kept for 5h. After the reaction was completed, the sample was washed and dried to obtain WO 3-x Nanosheets.

[0041] (2) Nano-Ag and Nano-CuI Co-loaded WO 3-x Preparation of composite nanomaterials

[0042] 100g WO 3-x The nanomaterial and 3.4g (20mmol) AgNO3, 9.9g (60mmol) KI, 4.8g (30mmol) CuSO4 were dispersed in 60mL deionized water, and 20mL ethanol and 15mL dimethylformamide were slowly added under magnetic stirring, and the magnetic stirring was continued for 5h, and then the sample was dried by centrifugation and vacuum drying. The sample was calcined at 200℃, 5% hydrogen + 95% argon or nitrogen atmosphere to obtain Ag / CuI / WO 3-x Nanomaterials, and WO 3-x The content is 92.6%, the Ag content is 2%, and the CuI content is 5.4%.

[0043] Ag / CuI / WO 3-x Nanomaterials catalyze the acidification reaction of alkynes with CO2

[0044] The Ag / CuI / WO obtained in Example 1-3 3-x Nanomaterial (100 mg) was added to a 25 mL Schlenk reaction bottle with phenylpropyne (1.0 mmol), Cs2CO3 (0.3910 g, 1.2 mmol), n-BuI (0.221 g, 1.2 mmol) and DMF (5 mL), and the reaction was sealed with a rubber stopper. The mixture was frozen in ice-salt water for 15 minutes, and the atmosphere was replaced with high-purity CO2 gas 5 times. The reaction mixture was heated to a certain temperature (100 ° C) under CO2 (99.999%, balloon) atmosphere and stirred for 15 hours. After the reaction was completed, water was added to the mixture and extracted with ethyl acetate five times. The combined organic layer was washed with a saturated NaCl aqueous solution and then dried with MgSO4. The solvent was then removed under reduced pressure to obtain a crude product, and the residue was purified by column chromatography (petroleum ether: EtOAc = 15:1) to obtain the desired product. The product was identified by nuclear magnetic resonance and mass spectrometry. When the catalyst needs to be recovered, firstly, high-speed centrifugation is performed to obtain a solid, which is then washed three times with ethanol and vacuum dried to obtain a recovered catalyst; the mother liquor obtained by centrifugation is treated normally to obtain the desired product.

[0045] Table 1 shows the Ag / CuI / WO with different Ag and CuI contents 3-x Effects of nanomaterials and dosage on the acidification reaction of alkynes with CO2.

[0046] Table 1 Effect of catalyst and catalyst dosage on reaction

[0047]

[0048] Catalyst Experiment Comparison

[0049] 1. WO 3-x Catalytic system research

[0050] Using the carboxylation reaction of phenylacetylene with carbon dioxide as a template, the WO was studied under fixed experimental conditions: phenylpropyne (1.0 mmol), Cs2CO3 (1.5 mmol), CO2 (1.0 atm, balloon), n-BuI (1.2 eq), 50 °C, solvent (5 mL), time 15 h. 3-x The effect of catalyst dosage on yield is shown in Table 2.

[0051] Table 2 Different dosages of WO 3-x Impact on reaction

[0052]

[0053] 2. Ag / WO 3-x Catalytic system research

[0054] Taking the carboxylation reaction of phenylacetylene with carbon dioxide as a template, under fixed experimental conditions: phenylpropyne (1.0mmol), Cs2CO3 (1.5mmol), CO2 (1.0atm, balloon), n-BuI (1.2eq), 50℃, solvent (5mL), time 15h, the effects of catalyst type and dosage on the yield were studied. The specific data are shown in Table 3. The fixed catalyst dosage was 100mg, and it was found that the loading of metallic silver in the catalyst had a significant effect on the yield. Ag / WO 3-x -2 (containing 0.5% Ag) showed the best effect, with a yield of 85%. Further increasing the amount of metallic silver loaded in the catalyst caused a sharp drop in the catalytic effect. When the metallic silver content in the catalyst is low, it mainly exists in the form of atomic clusters or extremely small particles. When the content of loaded silver in the catalyst increases, the particles of metallic silver increase, causing its catalytic effect to decrease rapidly. This shows that the existence form of metallic silver in the catalyst has a significant effect on the catalytic effect. Reducing the amount of catalyst to 50 mg, the reaction yield decreased slightly, and further reducing the amount of catalyst to 30 mg, the yield decreased to 63%.

[0055] Table 3 Effect of catalyst and catalyst dosage on reaction

[0056]

[0057]

[0058] From Table 2 and Table 3, we can see that Ag / WO 3-x The catalytic effect is better than that of pure WO 3-x The catalytic effect of Ag loaded on WO 3-x The catalytic performance of the esterification reaction of alkynes with CO2 on the nanosheets is better than that of the pure WO 3-x (WO 3-xThe main reasons for the good catalytic effect of tungsten trioxide with oxygen defects are as follows:

[0059] 1. Optimize active centers: Ag loading can provide more active centers, which can enhance the catalytic activity in the reaction. Silver can react with alkynes to form vinyl acetate compounds, thereby promoting the reaction.

[0060] 2. Enhance the ability to fix carbon dioxide: Ag loading helps to increase the adsorption and fixation capacity of carbon dioxide in the reaction system, providing more reaction substrates.

[0061] 3. Promote electron transfer: The interaction between Ag and tungsten trioxide can promote the transfer of electrons and improve the efficiency of the reaction.

[0062] 4. Provide a larger active surface area: Ag loaded on WO 3-x Nanosheets can provide a larger active surface area, thereby enhancing the effectiveness of catalytic reactions.

[0063] 3. CuI / WO 3-x Catalytic system research

[0064] Taking the carboxylation reaction of phenylacetylene with carbon dioxide as a template, the effects of the type and amount of catalyst on the yield were studied under fixed experimental conditions: phenylpropyne (1.0mmol), Cs2CO3 (1.5mmol), CO2 (1.0atm, balloon), 100℃, solvent (5mL), and time 15h. The specific data are shown in Table 4. The fixed catalyst dosage was 100mg, and it was found that the loading of metallic silver in the catalyst had a significant effect on the yield. CuI / WO 3-x -3 (containing 4.0% CuI) showed the best effect, with a yield of 76%. Further increasing the CuI loading in the catalyst decreased the catalytic effect. The reason is that when the CuI loading in the catalyst is too large, a large number of CuI particles will WO 3-x The catalyst was completely covered and agglomerated into larger particles, resulting in a decrease in its catalytic effect. When the catalyst dosage was reduced to 50 mg, the reaction yield was slightly reduced. When the catalyst dosage was further reduced to 30 mg, the yield was reduced to 61%.

[0065] Table 1 Effect of catalyst and catalyst dosage on reaction

[0066]

[0067] From Table 2 and Table 4, we can see that CuI / WO 3-x The catalytic effect is better than that of pure WO 3-x The catalytic effect of CuI on WO 3-x The catalytic performance of the esterification reaction of alkynes with CO2 on the nanosheets is better than that of the pure WO3-x (WO 3-x The reason why the catalytic effect of tungsten trioxide with oxygen defects is good is mainly due to the combined effect of the following factors:

[0068] 1. Increased surface active sites: CuI loaded on WO 3-x Nanosheets can provide more active sites, increasing the chances of catalytic reactions and thus increasing catalytic efficiency.

[0069] 2. Synergistic effect: CuI loaded on WO 3-x The nanosheets can form a synergistic effect with oxygen-deficient tungsten trioxide, improving the electron transfer rate and reaction activity during the catalytic reaction.

[0070] 3. Regulating the reaction path: CuI loaded on WO 3-x The reaction path can be regulated on the nanosheets, making the condensation and esterification reaction more inclined to produce the target product, thereby improving the catalytic effect.

[0071] Further comparison of the data in Tables 1, 3, and 4 shows that Ag and CuI are loaded on WO 3-x The catalytic effect of the esterification reaction of alkynes with CO2 on the nanosheets is better than that of single Ag or single CuI loaded on WO. 3-x The catalytic effect on nanosheets is better for the following reasons:

[0072] 1. Synergistic effect: Ag and CuI are two different catalysts that have a synergistic effect in catalytic reactions. Compared with a single catalyst, the two catalysts loaded together on the nanosheets may form more active sites and may interact with each other, thereby improving the reaction activity and selectivity.

[0073] 2. Electronic effect: WO 3-x Nanosheets are very active electron transport materials, which can form electron transfer paths between supported catalysts. Silver and CuI are loaded on WO 3-x The nanosheets can promote the reaction through electron transport and improve the reaction effect.

[0074] 3. Mesoscopic effect: The nanosheets have a special structure, a large specific surface area and a highly controllable morphology, which improves the dispersion and stability of Ag and CuI on the nanosheets, thereby enhancing the effect of the catalytic reaction.

[0075] That is, Ag and CuI are loaded on WO 3-x The better catalytic effect of the condensation and esterification reaction of alkynes with CO2 on nanosheets is due to the combined effects of synergistic effect, electronic effect and mesoscopic effect.

[0076] Optimization of reaction conditions

[0077] In order to obtain the best reaction conditions, under fixed conditions (experimental conditions: phenylpropyne (1.0 mmol), catalyst Ag / CuI / WO 3-x (Ag 0.5%CuI 7.1%) 50mg, CO2 (1.0atm, balloon), 100℃, solvent (5mL), time 15h), the effects of solvent type, base type and reaction temperature on the reaction yield were investigated. The specific results are shown in Table 5.

[0078] Table 5 Effect of solvent and catalyst dosage on the reaction

[0079]

[0080]

[0081] As shown in Table 5, when cesium carbonate (Cs2CO3) is used as a base, the excess amount of 1.2eq of the base is relatively appropriate. The type of solvent has a great influence on the yield of the reaction. The yield of highly polar solvents is generally good, which is mainly attributed to the good solubility of polar solvents for reaction substrates, bases, CO2, etc. Among them, in the reaction system with Cs2CO3 as a base, when the solvent is NMP (N-methylpyrrolidone), the best yield (88%) is shown. When screening different types of bases, the organic base TBD (1,5,7-triazabicyclo [4.4.0] dec-5-ene) can also obtain a moderate reaction yield in NMP solvent. With Cs2CO3 as a base, in NMP solvent, further increasing the temperature to 120°C, the yield is only slightly increased (89%), and the yield begins to decrease (82%) when the reaction temperature is reduced to 80°C; the yield is significantly reduced (36%) when the temperature is reduced to 50°C. It can be seen that the best reaction conditions are Cs2CO3 as base, NMP as solvent, and reaction temperature of 100°C.

[0082] In order to verify the catalyst Ag / CuI / WO 3-x The recyclability and practicality of (Ag 0.5%CuI 7.1%) were studied by recycling the recovered catalyst under the optimal reaction conditions and examining the reaction yield. Figure 3 It can be seen that after the catalyst is recycled for 5 times, the reaction yield can still be maintained at about 70%, indicating that the catalyst has good reusability.

[0083] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A nano-Ag and nano-CuI co-loaded WO 3-x Material, characterized in that The material includes WO 3-x Nanosheets, the WO 3-x The nanosheets are loaded with Ag and CuI; in the material, the content of Ag is 0.01-10%, the content of CuI is 0.05-10%, and the content of WO is 3-x The content is 80-99.4%.

2. Nano-Ag and nano-CuI co-loaded with WO as claimed in claim 1 3-x The method for preparing the material is characterized in that: The steps include: S1. Preparation of WO 3-x Nanosheets; S2. WO 3-x The nanosheets, AgNO3, KI and CuSO4 were dispersed in a solvent, and then ethanol and dimethylformamide solution were added dropwise. After stirring, the product was centrifuged and dried and calcined to obtain Ag / CuI / WO. 3-x Nanomaterials.

3. Nano-Ag and nano-CuI co-loaded WO according to claim 2 3-x The method for preparing the material is characterized in that: In step S1, WO 3-x The preparation method of the nanosheet is as follows: dissolving sodium tungstate dihydrate, adding acid solution and heating, and then washing and drying the product.

4. Nano-Ag and nano-CuI co-loaded WO according to claim 3 3-x The method for preparing the material is characterized in that: The acid solution is any one of concentrated hydrochloric acid, concentrated nitric acid and concentrated sulfuric acid.

5. Nano-Ag and nano-CuI co-loaded WO according to claim 3 3-x The method for preparing the material is characterized in that: WO 3-x During the preparation of the nanosheets, the acid solution is added and heated to 150-220°C and kept warm for 4-7 hours.

6. Nano-Ag and nano-CuI co-loaded WO according to claim 3 3-x The method for preparing the material is characterized in that: The ratio of sodium tungstate dihydrate to acid solution is: (1-5)mmol:(15-30)mL.

7. Nano-Ag and nano-CuI co-loaded WO according to claim 2 3-x The method for preparing the material is characterized in that: In step S2, WO 3-x The mass ratio of nanosheets, AgNO3, KI, and CuSO4 is: (50-150):(0.6-4):(6-12):(3-10).

8. Nano-Ag and nano-CuI co-loaded WO according to claim 2 3-x The method for preparing the material is characterized in that: In step S2, calcination is performed under an atmosphere of 1-10% hydrogen and 90-99% argon or nitrogen.

9. Nano-Ag and nano-CuI co-loaded WO according to claim 2 3-x The method for preparing the material is characterized in that: In step S2, the calcination temperature is 150-300°C.

10. The nano-Ag and nano-CuI co-loaded WO as claimed in claim 1 3-x Material or nano-Ag and nano-CuI co-loaded WO prepared by any preparation method according to claim 2-9 3-x Application of materials in catalyzing the acidification reaction of alkynes with CO2.